Encyclopedia of thermal packaging. Set 1, Volumes 1-6 - Bar-Cohen, Avram, 1946- (World Scientific Pub. Co., 2013)
The first set of the Encyclopedia, Thermal Packaging Techniques, focuses on the technology "building blocks" used to assemble a complete thermal management system and provide detailed descriptions of the underlying phenomena, modeling equations, and correlations, as well as guidance for achieving the optimal designs of individual "building blocks" and their insertion in the overall thermal solution. Specific volumes deal with microchannel coolers, cold plates, immersion cooling modules, thermoelectric microcoolers, and cooling devices for solid state lighting systems, as well as techniques and procedures for the experimental characterization of thermal management components. These "building blocks" are the essential elements in the creation of a complete, cost-effective thermal management system. The four sets in the Encyclopedia of Thermal Packaging will provide the novice and student with a complete reference for a quick ascent on the thermal packaging "learning curve", the practitioner with a validated set of techniques and tools to face every challenge, and researchers with a clear definition of the state-of-the-art and emerging needs to guide their future efforts. This encyclopedia will, thus, be of great interest to packaging engineers, electronic product development engineers, and product managers, as well as to researchers in thermal management of electronic and photonic components and systems, and most beneficial to undergraduate and graduate students studying mechanical, electrical, and electronic engineering.
Keywords: Electronic packaging.; Heat sinks (Electronics); Insulation (Heat); elektronické knihy; electronic books